2020
DOI: 10.1002/jclp.22941
|View full text |Cite
|
Sign up to set email alerts
|

Parent and child emotion and distress responses associated with parental accommodation of child anxiety symptoms

Abstract: Objective: Parental accommodation contributes to the maintenance of child anxiety and related symptoms. The current study examines the contributions of parent and child factors to parental accommodation in a sample of anxious youth. Methods: Sixty-four treatment-seeking youth (6-16 years) and their mothers, as well as a subset of fathers (N = 41) reported on parental accommodation, parental distress and emotion regulation, child psychopathology, child externalizing behaviors, and child intolerance of uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
(113 reference statements)
4
14
3
1
Order By: Relevance
“…Parental anxiety has also been found to be associated with youth anxiety [21], and may thus be an important confounding factor explaining the directional relationship between family accommodation and youth anxiety. However, other studies have not found an association between parental distress and family accommodation [12,43]. Thus, it is uncertain to what degree the findings in the present study are confounded by changes in parent mental health.…”
Section: Discussioncontrasting
confidence: 70%
“…Parental anxiety has also been found to be associated with youth anxiety [21], and may thus be an important confounding factor explaining the directional relationship between family accommodation and youth anxiety. However, other studies have not found an association between parental distress and family accommodation [12,43]. Thus, it is uncertain to what degree the findings in the present study are confounded by changes in parent mental health.…”
Section: Discussioncontrasting
confidence: 70%
“…Recent research has suggested that it may not be parental distress per se that influences FA but parental perceptions of child anxiety symptoms. O'Connor et al (2020) reported that contrary to expectations and not in line with other studies, FA was not linked to parental distress or emotional regulatory difficulties in the sample of parents of anxious children. Instead, findings indicated that maternal perception of child distress was more influential in determining the level of FA.…”
Section: Self-as-contextcontrasting
confidence: 92%
“…When examining parent-related clinical correlates, our results on fathers indicated that fathers who rated themselves as more anxious were also more likely to engage in higher levels of accommodation, including modification of family routines and to report negative child consequences, such as temper tantrums, when they did not accommodate. Although our findings on fathers are in line with our hypothesis, they are also at odds with the findings of a recent study that did not find a significant association between fathers' anxiety symptoms and fathers' overall accommodation in a smaller sample of 41 fathers [41]. In contrast to fathers, our results on mothers indicated that mothers' overall accommodation, including participation, modification, distress, and consequences, was not related to mothers' self-reported anxiety symptoms.…”
Section: Correlates Of Fathers' and Mothers' Facontrasting
confidence: 78%